1998
DOI: 10.1001/jama.279.11.839
|View full text |Cite|
|
Sign up to set email alerts
|

Sodium Reduction and Weight Loss in the Treatment of Hypertension in Older Persons

Abstract: Context.-Nonpharmacologic interventions are frequently recommended for treatment of hypertension in the elderly, but there is a paucity of evidence from randomized controlled trials in support of this recommendation.Objective.-To determine whether weight loss or reduced sodium intake is effective in the treatment of older persons with hypertension.Design.-Randomized controlled trial.Participants.-A total of 975 men and women aged 60 to 80 years with systolic blood pressure lower than 145 mm Hg and diastolic bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
201
1
8

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 1,057 publications
(215 citation statements)
references
References 38 publications
5
201
1
8
Order By: Relevance
“…Our findings are consistent with previous trials utilizing lifestyle interventions in subjects with specific risk factors or with known CVD 30, 31, 32, 33, 34, 35. However, these studies have not been performed in an otherwise relatively healthy population where the goal was not prevention of disease, but to maintain ideal health.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are consistent with previous trials utilizing lifestyle interventions in subjects with specific risk factors or with known CVD 30, 31, 32, 33, 34, 35. However, these studies have not been performed in an otherwise relatively healthy population where the goal was not prevention of disease, but to maintain ideal health.…”
Section: Discussionsupporting
confidence: 91%
“…Long-term high salt intake is an important risk factor for hypertension (5) . Several large randomised trials and meta-analyses of trials have shown that a reduction in salt intake lowers blood pressure in hypertensive individuals (6,29) . The climate in Napo County is like the south subtropics.…”
Section: Discussionmentioning
confidence: 99%
“…These associations were independent of age, socioeconomic status and other major risk factors for hypertension. Numerous epidemiologic studies [1][2][3][4][5][6]12,13,[21][22][23][24] and interventional trials [25][26][27][28] have demonstrated that weight change and excess weight plays a major role in determining BP levels, particularly among individuals with high BP. Few studies have evaluated the impact of weight and weight change on BP in normotensive individuals.…”
Section: Discussionmentioning
confidence: 99%